1998
DOI: 10.1161/01.hyp.31.5.1111
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Production of Angiotensin II in the Isolated Perfused Rat Heart

Abstract: Abstract-We used a modification of the isolated perfused rat heart, in which coronary effluent and interstitial transudate were separately collected, to investigate the localization and production of angiotensin II (Ang II) in the heart. During combined renin (0.7 to 1.5 pmol Ang I/mL per minute) and angiotensinogen (6 to 12 pmol/mL) perfusion (4 to 8 mL/min) for 60 minutes (nϭ3), the steady-state levels of Ang II in interstitial transudate in two consecutive 10-minute periods were 4.3Ϯ1.5 and 3.6Ϯ1.5 fmol/mL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 37 publications
2
40
1
1
Order By: Relevance
“…However, we and others have obtained similar results for local Ang formation with different renin sources in the rat model. 6,[27][28][29] Recently, Hu et al 30 showed identical hemodynamic and hormonal responses to 14-day infusions of renin or Ang II in conscious rats. They concluded that tissue-bound renin does not play a unique role in promoting cardiovascular, renal, hormonal, or drinking responses.…”
Section: Discussionmentioning
confidence: 96%
“…However, we and others have obtained similar results for local Ang formation with different renin sources in the rat model. 6,[27][28][29] Recently, Hu et al 30 showed identical hemodynamic and hormonal responses to 14-day infusions of renin or Ang II in conscious rats. They concluded that tissue-bound renin does not play a unique role in promoting cardiovascular, renal, hormonal, or drinking responses.…”
Section: Discussionmentioning
confidence: 96%
“…Alternatively and perhaps more likely in view of the rapid activation process, cell-activated prorenin may contribute to intracellular angiotensin generation before its destruction. Several studies have provided evidence for intracellular angiotensin generation (17,32,42), and ANG II is known to activate intracellular AT 1 receptors in the cytosol and nucleus (23,27). In the absence of local renin synthesis, such intracellular angiotensin generation will depend on the uptake of circulating renin or prorenin.…”
Section: Discussionmentioning
confidence: 99%
“…22 Local angiotensin formation in the heart may contribute to the pathogenesis of cardiac hypertrophy, congestive heart failure, and tissue remodeling. 23 We have reported that rat and human blood vessels produce aldosterone.…”
Section: Discussionmentioning
confidence: 99%